I Guess What You Say is True. Issue 3 (3rd July 2017) - Driscoll, Oliver
ABSTRACT: This work of non-fiction struggles with the technical and ethical difficulties of representing the former Yugoslavia, an area that has experienced deep trauma and that is at a remove from the author's experience. The author-narrator confronts the challenges of representing others' trauma in an oblique way: focusing on his own life in Melbourne and his responses to Yugoslavia's past; critiquing narrative forms and particular literary works that represent the trauma, namely those of the Bosnian-American writers Aleksandar Hemon and Semezdin Mehmedinović; and acknowledging the vexed framework of the creative-writing PhD for which the reflection was produced.